Upaya Meningkatkan Minat Belajar IPS pada Siswa dengan Media Pembelajaran Power Point - Oktapia, Dewi; Asmara, Yeni; Yati, Risa Marta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of powerpoint learning media on student interest in social studies subjects VIII in Sumber Harta State Junior High School. The research method used is pure experimentation. Determination of the sample is done by using simple random sampling technique from the population of all students of class VIII, and 50 students selected as samples are class VIII A (experimental class) given learning treatment with powerpoint learning media and class VIII B (control class) is not treated. Data collection techniques in the study using a questionnaire that has been tested for validity and reliability testing. The results of the study using the percentage formula showed that 23 students were categorized as very interested (SB) with a percentage of 92% and 2 students were categorized as interested (B) with a percentage of 8%, while students who were categorized as less interested (KB) and students who were not interested (TB) ) as much as 0% or none. Conclusion, there is a significant influence of learning media using powerpoint on students' learning interest in social studies Keywords: Influence, Powerpoint, Interest in Learning.